Pengaruh Edukasi Gizi Terhadap Pengetahuan, Pola Makan Dan Kadar Glukosa Darah Pasien Diabetes Melitus Tipe 2 RSU Kota Mataram Dengan Provinsi NTB - Susilawati, Wulandari Dewi; Hasanah, Uswatun (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2023)
The phenomenon of diabetes mellitus from year to year an increasing number. One major factor is the lack of knowledge in conducting therapy in patients with diabetes mellitus diit so may lead to increased blood sugar levels. The aim of this study was to determine the effect of nutrition education to increase the knowledge, dietary compliance and uncontrolled blood sugar levels Type 2 Diabetes Mellitus Outpatient in Kota Mataram Dg Provinsi NTB Public Hospital Jeneponto. The design of this research was experimental studies with pre experimental designs One Group Pretest And Postest Design. Sampling was conducted using purposive sampling technique with a sample of 30 people. Data was collected by the secondary data and primary data. The dietary pattern data was collected by 24 hours recall questionnaire, blood glucose level of patients were measured by blood glucose meter. While the knowledge of patients were collected by interview using questionnaire.given before and after the education. Height and weight of patients were measured by scale and microtoice. The secondary data are the description of hospital and laboratory result data obtained from the hospital. Data analysis was performed by Mc Nemar test.The results showed, after education, knowledge of patients categorized sufficiently increased (p = 0.031), from 33.3% to 53.3%, as well as the diet of patients (p = 0.003), from 23.3% to 60 , 0% categorized fairly, as well as the patient's blood sugar levels were controlled (p = 0.000), from 3.3% to 46.7%. It is recommended to patients to better manage diet to control blood sugar levels with the help of physical activity and obedient in taking the drug.